DEI Excavations on the Southwestern Slope of Mount Zion (2015–2019) - Vieweger, Dieter; Zimni, Jennifer; Schöpf, Friederike; Würz, Michael (Archäologischer Anzeiger, 2020)
The excavations of the GPIA Mount Zion project are located around the Protestant Cemetery in Jerusalem. Three areas reveal archaeological remains dating from the Iron Age II up until the Islamic period. After reinvestigating the area of the »Gate of the Essenes« the GPIA excavated further living quarter structures, mainly dating into the Early Roman as well as into the Byzantine era. The results shed new light on the course of the ancient city walls (Iron Age – Ayyubid) as well as on the population living on Mount Zion in Roman and Byzantine times.